Seasonal variation of the zooplankton communities’ diversity in ponds of the Atlantic Forest - Maria Eduarda Turcato de Souza; Natan Guilherme Dos Santos; Laura Jardim Chiarelli; Maria Stela Maioli Castilho Noll (Acta Limnologica Brasiliensia, 2025)
Abstract: Aim This study analyzed the structure and seasonal variation of the zooplankton community in five ponds in a preserved Atlantic Forest environment in Brazil, the Betary Reserve. Methods Sampling took place in March and September 2022, January and July 2023, covering the summer (rainy) and winter (dry) seasons. Vertical trawls were carried out with a 45μm plankton net and, at the same points, physical-chemical parameters of the water were measured with a multi-parameter probe. Results Fifty-nine taxa were recorded, distributed between Copepoda (1), Cladocera (5) and Rotifera (53). Among them, the families Lecanidae, Brachionidae and Trichocercidae were the most representative in number of species. Mesocyclops longisetus longisetus, Ceriodaphnia cornuta and Brachionus quadridentatus were present in all samples. The highest richness was observed in January/23. There was a difference in the composition of the assemblage between the seasons. Conductivity and temperature were structuring factors for some populations. Conclusions The study pointed to a high diversity of the zooplankton in ponds within the Atlantic Forest, demonstrating the importance of preserved sites for the conservation of the biodiversity of this threatening biome. Further studies are needed to understand the distribution pattern of zooplankton species, the seasonal variation and their relationship with the physical-chemical parameters of the water.